Morphological and karyotype diversity in populations of four Silene species (Caryophyllaceae) - Keshavarzi, Maryam; Sheidai, Masoud; Gholipour, Abbas (Acta Biologica Szegediensis, 2014)
Karyotype and morphometric studies were performed on 14 and 24 Iranian populations of 4 Silene (Caryophyllaceae,Sect. Auriculatae) species. Phenetic study of 24 populations of S. commelinifolia, S. eremicana, S. lucida and S. nurensis from different locations of Iran revealed that a lot of morphological characters as basal and caulinal leaf shape, width and length, capsule shape and condition in calyx, epipetalus stamens to alternate ones, alar pedicel length, lateral pedicel length, epipetalus filament length to claw length and calyx gap length are of taxonomic importance. S. nurensis possessed a chromosome number 2n=2x=24, S. lucida and S. eremicana possessed a chromosome number 2n=4x=48, while S. commelinifolia var. commelinifolia and S. commelinifolia var. ovatifolia populations were diploid and tetraploid. The chromosomes were mainly metacentric or sub-metacentric and their size varied from 1.21 μm in S. nurensis to 3.96 μm in S. commelinifolia. The total size of the chromosomes differed significantly in short and long arm size, indicating the role of quantitative genomic changes in the Silene species diversification. The Silene species were placed in 1A and 1B classes of Stebbins karyotype symmetry. Presence of B chromosome is recorded for the first time for S. commelinifolia. Clustering and ordination methods showed karyotype distinctness in the investigated species.